Intestinal Helminth Infections and Associated Risk Factors among School-Aged Children of Bamendjou Community, West Region of Cameroon - Matsinkou Mba Rosine Ruth; Yamssi Cedric; Mbong Erica Malla; Noumedem Anangmo Christelle Nadia; Tateng Ngouateu Aime; Megwi Leonelle; Vincent Khan Payne (Journal of Parasitology Research)
Background. Infection with intestinal nematodes is of major public health concern worldwide, and school-age children and pregnant women are the principal victims. The present study was undertaken to provide baseline information on the status of gastrointestinal nematodes among school-age children in Bamendjou. Material and Methods. Four hundred and ninety-three (493) stool samples were collected from school children in six (6) different schools (two nursery, two primary, and two secondary schools). Qualitative and quantitative analyses of stool samples were done using the simple flotation and McMaster count techniques, respectively. Results. Among the 493 participants, 57 (11.6%) stool samples were positive for at least one nematode species. Four nematodes are as follows: Ascaris sp., Trichuris sp., hookworms, and Strongyloides sp. with respective prevalence and intensities of infection of 6.1% and 2260±6377.98, 3.4% and 223.53±264.054, 3.0% and 416.67±427.061, and 0.2% and 200±00, respectively. The data on the prevalence of nematodes with respect to sex showed that females (13.1%) were more infected than males (12.2%) (P>0.05). Furthermore, with respect to age, older children were more infected than younger ones. Cases of double parasitism were encountered with a prevalence of 1.2%. According to the fecal concentration of eggs, 61.90% of the infections were light. Risk factors such as drinking water from streams and not wearing shoes all the time were significant with infections. Conclusion. The relatively low overall prevalence (11.6%) obtained in this study shows that the national deworming campaign is proving effective, though a more holistic approach is required to prevent infections from bouncing back after such campaigns.